Dynamics of hemostasis system parameters in assessing the risk of complications in the patients with acute myocardial infarction receiving antiplatelet therapy - T. R. Gvindzhiliya; I. M. Kuzmina; E. V. Klychnikova; E. V. Tazina; A. A. Kochetova; N. A. Muradyan; A. S. Bogdanova (Трансплантология (Москва), 2024)
Background. Current treatment of patients with myocardial infarction is based on the strategy of early invasive coronary intervention in combination with dual antiplatelet therapy - with acetylsalicylic acid and a P2Y12 blocker of platelet adenosine diphosphate receptors. In patients with thrombosis of the infarct-related artery, the phenomenon of “slow/ no reflow” (slowing of blood flow due to distal embolization of the artery), inhibitors of glycoprotein IIb/IIIa platelet receptors are administered as additional disaggregant therapy. In patients undergoing standard antiplatelet therapy in combination with glycoprotein IIb/IIIa inhibitors, there is a risk of hemorrhagic complications, therefore, monitoring of hemostasis parameters is necessary. Currently, there are no standard approaches to monitor the antiplatelet therapy.Objective. To study the dynamics of hemostatic system parameters in patients with acute myocardial infarction during antiplatelet therapy.Material and methods. We assessed platelet aggregation with 10 µmol of adenosine phosphate as an inducer in patients with ST-segment elevation myocardial infarction with different options of standard antiplatelet therapy in combination with GPIIb/IIIa inhibitors. Group 1 included 20 patients on dual antiplatelet therapy (clopidogrel 75 mg + acetylsalicylic acid 100 mg) + GPIIb/IIIa inhibitor (tirofiban). Group 2 included 15 patients on dual antiplatelet therapy (ticagrelor 180 mg + acetylsalicylic acid 100 mg) + GPIIb/IIIa inhibitor.Results. While on antiplatelet therapy the patients in both groups 1 and 2 demonstrated a decrease in platelet aggregation ability under the impact of adenosine phosphate, relative to the norm: 38 (21;43) % and 14 (11;15) %, respectively, the norm being 79 (73;84) % (p<0.05). Meantime, no thrombotic events in the form of stent thrombosis were noted, which indicated antiplatelet therapy efficacy. In an intragroup comparison, the decrease in the platelet aggregation ability was most pronounced in group 2 (p<0.05). By the 7th day of myocardial infarction, the platelet aggregation had continued to decrease to 26 (17;43) % in group 1, to 10 (7;11) % in group 2. The most pronounced effect of antiplatelet therapy was observed in group 2 (p<0.05), which was manifested by a statistically significant decrease in platelet aggregation ability under the impact of 10 µmol of adenosine phosphate.Conclusions. While studying the hemostasis system changes over time in patients with myocardial infarction receiving antiplatelet therapy, we have found that making the platelet aggregation ability assessment with 10 µmol of adenosine phosphate as an inducer is possible to identify the effect of medications. However, further studies including larger patient groups are needed to determine the target values of platelet aggregation with 10 µmol of adenosine phosphate and assess the therapy efficacy.